'Con la propria mia voce parli'. Literary Genres, Portraits, and Voices in Giuseppe Betussi's Imagini del tempio (1556). (March 2014) - Pich, Federica
<x content-type="archive" xml:space="preserve">Abstract</x> Giuseppe Betussi's Imagini del tempio della signora donna Giovanna Aragona (1556) offers a privileged insight into the inner workings of encomium as a crucial self-authorizing experience in Renaissance culture. In this perspective, the paper focuses on: a) the strategic blending of literary genres as a response to the tensions of a challenging editorial market; b) the pivotal role of figurative metaphors in the self-depiction of celebrative texts and their connection with the memorial and allegorical dimensions; and c) the multiplication of textual voices and layers as a means of staging celebration itself as an ongoing performance, combining monumental accomplishment and verbal dynamism. It considers the question of why Betussi seemingly connects a small corpus of lyric texts (the sonnets quoted in the Imagini) to a major collection (Ruscelli's 1554 Tempio alla divina signora Giovanna d'Aragona) by means of a dialogue between Truth and Fame and proposes that the figure of Truth enables Betussi to modulate one single voice from the apparent interaction of many, ultimately building on well-established collective models to create a solo encomiastic anthology.